Analisis Rasio Profitabilitas Sebagai Alat Ukur Untuk Menilai Net Profit Margin, Return on Assets, Dan Return On Equity Pada PT Toba Pulp Lestari Tbk Periode 2020-2023 - thalia (Jurnal Akuntansi Nommensen, 2023)
This final report is entitled "Analysis of Profitability Ratios as a Measuring Tool for Assessing Net Profit Margin, Return on Assets, and Return on Equity at PT Toba Pulp Lestari Tbk for the 2020-2023 Period". This research aims at the profitability ratio level of Net Profit Margin, Return On Assets and Return On Equity. The reason for choosing this title is because there is a phenomenon in PT Toba Pulp Lestari Tbk financial reports for the 2020-2023 period, namely that the company's Total Assets and Sales are experiencing fluctuations, while the company's Net Profit continues to decline. For this reason, it is necessary to carry out ratio analysis in the financial statements. The type of data used in research is quantitative data. The data source used is secondary data, namely the financial report at PT Toba Pulp Lestari Tbk. Data collection was carried out using documentation techniques sourced from www.tobapulp.com. The data processing technique used is descriptive analysis and ratio analysis in terms of profitability ratios which include Net Profit Margin, Return On Assets and Return On Equity. Based on the results of calculations and analysis, it was concluded that the profitability ratio levels of Net Profit Margin, Return On Assets and Return On Equity were considered not good because they were below industry standard ratios.